THE NEW DICKINSONID FROM THE UPPER VENDIAN OF THE WHITE SEA WINTER COAST (RUSSIA, ARAKHANGELSK REGION) - Ivantsov A.Yu. (My University, 1999)
A description and reconstruction of the new fossil are based on the rounded isometric imprints which are composed of two rows of transverse elements. The elements are arranged in the manner of glide reflection symmetry. The lateral flanks of the elements are pointed and curved in identical directions. It is suggested tha this fossil was preserved as imprints of different appearances (positive and negative) including «trilobite-like» forms. The relief of the imprints could be positive or negative. The fossils occur as isolate imprints or in accumulations.
Keywords: Vendian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский